Whose Play Scripts Are Being Published? A Diversity Audit of One Library's Collection in Conversation with the Broader Play Publishing World. Issue 4 (1st October 2020) - Stone, Scott M.
Abstract: This study is a diversity audit of play script orders during FY2011 and FY2019 to determine if University of California, Irvine Libraries' orders had shifted to reflect the increased demand for diverse playwrights. The audit also examined the larger publishing landscape for play scripts during these specific years to determine if plays by diverse playwrights were being published and available for acquisition. The audit demonstrates that both the play script orders and publishing landscape have greatly diversified; however, further work needs to be done to continue diversifying local acquisitions with what is being published, so that library collections of play scripts reflect the university and country's demographics.